2015
DOI: 10.1177/1470595815572170
|View full text |Cite
|
Sign up to set email alerts
|

Social climate and job control as mediators between empowering leadership and learning from a cross-cultural perspective

Abstract: The purpose of this article is to examine the direct effects of empowering leadership on learning and the indirect or mediating role of social climate and job control from a cross-cultural perspective. Questionnaires were distributed to two furniture retail stores in Sweden and two stores in China belonging to the same company. The final sample consisted of 483 participants from the Chinese and 254 participants from the Swedish stores. The results of the structural equation modeling showed that there was a dir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
12
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 42 publications
2
12
0
Order By: Relevance
“…Employees have more opportunities to perform various tasks and accumulate mastery experience. Jonsson et al (2015) found that there was a direct relationship between empowering leadership and learning (both in Swedish and Chinese samples). An empirical study from China also proved that empowering leadership positively affects followers’ role breadth self-efficacy ( Li et al, 2015 ).…”
Section: Theoretical Background and Hypotheses Developmentmentioning
confidence: 93%
“…Employees have more opportunities to perform various tasks and accumulate mastery experience. Jonsson et al (2015) found that there was a direct relationship between empowering leadership and learning (both in Swedish and Chinese samples). An empirical study from China also proved that empowering leadership positively affects followers’ role breadth self-efficacy ( Li et al, 2015 ).…”
Section: Theoretical Background and Hypotheses Developmentmentioning
confidence: 93%
“…Similarly, employees tend to feel more in control of how to allocate their energy to different work activities to the extent that they believe their organisation actively supports their interests ( Jonsson et al, 2015). Conversely, to the extent that employees sense that their organisation is not preoccupied with their success and fails to accommodate their needs, the associated sense of isolation may create a fear about their ability to meet formal job expectations (Latorre et al, 2016), and accordingly, leveraging their positive job energy towards helping activities that go beyond their formal job duties becomes a less attractive scenario (Rich et al, 2010).…”
Section: Moderating Role Of Collectivistic Orientationmentioning
confidence: 99%
“…Along similar lines, Remneland-Wikhamn and Wikhamn (2011) emphasized the "critical" role of organizational climate in the implementation of open innovation. This paper argues that empowering leaders create an organizational climate that encourages and involves followers to participate in knowledge exploration and exploitation ( Jönsson et al, 2015). In such a climate, referred to as employee involvement climate, employees enjoy the autonomy to participate in decision-making, have access to information sources for their acquisition and utilization and are motivated to carry out activities to achieve organizational goals (Riordan et al, 2005).…”
Section: Introductionmentioning
confidence: 99%